Shifting identities: An exploration of the possibilities for a syncretic Afrikaans theatre by means of three case studies "“ Hex (2003), Lady Anne (2007), Ekspedisies (2008) - Gehring, Heike (Rhodes University, Faculty of Humanities, Department of Drama, 2016)
This thesis investigates the possibilities for syncretic Afrikaans language theatre within a post-1994 South African society. The research sets out to explore in what manner theatre can be language-specific, while at the same time being able to cross language contexts. This exploration is driven by the wish to develop strategies for creating Afrikaans theatre that is able to reflect on a society "united in diversity" . In this regard it is argued that for theatre to be able to both retain and cross language barriers, processes of bonding and bridging are necessary. The thesis sets out first to explain why these processes are required and then to suggest ways in which such processes can be implemented in practice. A triangular approach is used, in which conceptual and theoretical frameworks are developed to reflect on actual theatre practices. Three of my own productions are used as case studies, namely Hex (2000; 2003), Lady Anne (2007) and Ekspedisies (2008). These productions can be understood to be "boundary objects" in Henk Borgdorff's (2012: 177) sense of the word, in that they fulfil a dual function: they are artistic productions that can also be reconstituted to serve a research purpose beyond the productions themselves. All three works were first created for public consumption before becoming cases for this thesis. Many of the strategies that were developed and tested in creating these productions are examples of ways in which bonding and bridging in Afrikaans language theatre can be understood. Chapter One of the thesis contextualises the political currents and events that necessitated the impulse towards "bonding and bridging" . In this case the political and ethical impetus behind the practical explorations has been related predominantly to the democratisation of South African society, in which a paradigm shift happened from viewing the Afrikaans language as one over many to one amongst many. Within a multilingual South Africa, concerns are raised about ways in which to create theatre in South African languages other than English (often understood to be the only possible bridging language) that are able to cross language divides. Following this introduction to language-related concerns, Chapter Two explains how the shift from apartheid to democracy made space for shifts in identity "“ on personal as well as institutional levels: a progression from essentialised notions of culture to the celebration of plurality. This progression is then related to theatre, with an explanation of how the post-1994 theatre landscape demanded a reimagining of the form and function of theatre. In this re-imagination the notion of a "third space" is important; something that is introduced in this chapter as an alternative to polarised identity constructions. The function of the "third space" as an in-between space and a meeting point for diverse people and entities is a strong underlying theme of this thesis and it serves as a reoccurring touchstone to the ideas put forward. Chapter Three discusses the South African arts festival culture and its contribution to the South African theatre landscape. Particular focus is placed on the Klein Karoo National Arts festival (KKNK) as a platform for the development of the Afrikaans language within a post-1994 context. What is emphasized in particular is the attempt by the KKNK festival to be linguistically and culturally exploratory and inclusive in the face of language protectionism. After the contextual background of the first three chapters, the thesis shifts to an analysis of theories related to "hybridity" and "syncretism" . In Chapter Four the argument is put forward that of the various inclusive performance and theatre models that represent a multicultural society, the most responsive forms are those that are syncretic and hybrid. Principles that can contribute to the unification and merging of diverse and polarized societal groups are described, and suggestions are made for possible ways to bring about bonding and bridging within cultural practices. Having introduced these principles, examples are offered of how these theories might be understood in other disciplines, namely, religious studies, anthropology, history and a range of cultural practices. Following this broad discussion, Chapter Five describes syncretism and hybridity more specifically in theatre by means of relevant examples. Taking the discussion further into the realm of application, Chapter Six offers an overview of "workshop theatre" , "translation" and "collage making" as strategies for putting theories of hybridity and syncretism into practice. This is followed (in Chapters Seven, Eight and Nine) by a discussion of the three productions (Hex, Lady Anne and Ekspedisies) as case studies that demonstrate how these theories can be understood in practice. Practical strategies for bridging language divides are foregrounded, such as code switching as an approach for enabling a "co-habitation" of languages; physical theatre as a means for crossing language divides; and the creation of more than one language version of a production as a tactic to accommodate shifting contexts. Following on from the discoveries made in the foregoing chapters, I conclude that theories and practices related to notions of "third space" , "hybridity" and "syncretism" are ideal for creating theatre forms (in the Afrikaans language in particular) that can truly reflect a South African society which is "united in diversity" . The thesis ends by offering suggestions for ways in which new, future identities, can be developed.
Keywords: Uncatalogued